DIFFERENCES IN KNOWLEDGE, PREPAREDNESS, PERCEIVED RISK, AND PREVENTIVE BEHAVIOR IN IMPLEMENTING HEALTH PROTOCOLS BETWEEN POST INFECTED AND NEVER INFECTED WITH COVID-19 IN POLDA ACEH - Maulita; Agussabti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This study aims to determine differences in knowledge, preparedness, perceived risk, and preventive behavior in implementing health protocols between post-infected individuals and those who have never been infected with Covid-19 at the Aceh Regional Police. This study was obtained by means of purposive sampling involving 330 respondents, divided into 165 respondents who had been infected with COVID-19 and 165 who had never been infected with COVID-19 with a validity value above 0.3 and a Cronbach alpha value above 0.6. The data collection technique used a questionnaire/questionnaire and the data analysis technique used the chi-square test. The results showed that knowledge, preparedness, perceived risk, and preventive behavior of respondents who had been infected with Covid-19 were better and had a different significance value below 0.05.